Special issue : who belongs? : immigration, citizenship, and the constitution of legality - Sarat, Austin (Studies in law, politics, and society, 2013)
The objective of "Studies in Law, Politics, and Society" is to provide a vehicle for the publication of scholarly articles within the broad parameters of interdisciplinary legal scholarship. Whereas other law related publications publish within a single domain - the humanities, social science, or legal doctrine. Studies seeks to bridge those divides. We encourage submissions from a broad range of legal scholars and welcome articles exemplifying different theoretical perspectives and methodological approaches. We welcome submissions from an international group of scholars.